Longing for the Mongrel - April Munson (Revista Electrónica Interuniversitaria de Formación del Profesorado)
Throughout the United States, there is a strong push for development and implementation of hybrid (blended) and online courses in higher education. Campuses attach themselves to a variety of programs to assist this occurrence, and training for faculty on how to use the programs happen regularly. However, despite the call to do it, and the offering of the tools, many are still left uncertain on how to move an imagined online course beyond repositories of data. Knowing how to use tools of technology is not enough. The first step is to revisit what it means to teach and learn. This article describes the reconceptualization of teaching and learning that is ongoing in the implementation of a hybrid seminar course in art education by a technology trainee.